Day 1 Tue, March 27, 2018 2018
DOI: 10.2118/189929-ms
|View full text |Cite
|
Sign up to set email alerts
|

Next-Generation Release Device: Strong, Safer, Efficient, and Rigorously Qualified

Abstract: A new high-strength electrical release device has been developed that supersedes the typical weakpoint and achieves the same strength as the tool tension rating. A stronger release device facilitates running heavier tools on wireline, along with the ability to run significantly longer gun strings, which increases operational efficiency. The release device was subjected to a rigorous qualification program conducted to ensure the highest safety and reliability of this device under demanding conditions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…It is found that, among the downhole robots, only telescopic downhole robots can meet the drilling requirements. 7 However, the telescopic type of downhole robot is still in the development stage. The high temperature and high pressure resistance of the sealing structure is one of the main reasons restricting the application of telescopic type of downhole robot.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that, among the downhole robots, only telescopic downhole robots can meet the drilling requirements. 7 However, the telescopic type of downhole robot is still in the development stage. The high temperature and high pressure resistance of the sealing structure is one of the main reasons restricting the application of telescopic type of downhole robot.…”
Section: Introductionmentioning
confidence: 99%